Bullied, hawked, and scrutinized: Adult literacy practitioners’ affective reactions to state and institutional power - Amy Pickard (Adult Education Research Conference, 2018)
This study explores adult literacy practitioners’ affective responses to contemporary policy regimes, in order to inform efforts to improve working conditions for practitioners and, by extension, the educational experiences of learners.
Keywords: adult literacy; policy; critical ethnography; working conditions; accountability